La glossolalia, i qualia e la semiotica del sentimento - Harkness, Nicholas (Rivista Italiana di Filosofia del Linguaggio, 2020)
Glossolalia, or “speaking in tongues”, is a global Christian phenomenon. The stereotypical image of glossolalia is one of emotionally overwhelming contact with the deity caused by the direct intervention of the Holy Spirit into human speech behavior. For the linguist, glossolalia consists of language-like vocalizations without denotational “content”. For the glossolalist, the utterances contain divine messages that can be revealed through interpretation. This paper explains the process of verbal decomposition and recomposition, as practitioners shift their orientational focus from the narrow semiotic domain of denotation to the diffuse pragmatic domain of feeling, and then back again. Emotions – as both felt and lexicalized – serve as points of orientation throughout the process. Drawing on ethnographic data from South Korea, where Protestants practice glossolalia across denominations and congregations, this paper elucidates the systematic but covert cultural processes that mediate between the more overt forms of lexicalization of “emotion words” and speaker-focal expressions of “emotivity” or “emotionality”.